Elderly musculoskeletal disease burden in Karachi, Pakistan: Associations and implications for developing countries - Sabzwari, Saniya (Aging Med (Milton), 2020)
OBJECTIVE: The global rise in the older population has increased the rates of osteoporosis and osteoarthritis, conditions that impact mobility and functionality. There is limited data on musculoskeletal disease in older populations residing in developing countries. METHODS: A community‐based study using multistage cluster random sampling of older individuals was conducted in Karachi. Predefined criteria were used for osteoporosis and osteoarthritis. Gait assessment was performed. RESULTS: More than half of the participants were females and 53% reported illiteracy. Around 30% had osteoporosis and two‐thirds had osteoarthritis. Multivariate analysis showed associations of female sex, Pashtun ethnicity, illiteracy, and hypertension with the combined variable of osteoporosis and osteoarthritis. CONCLUSIONS: The prevalence of osteoarthritis was higher than in other regional studies. Presence of both osteoporosis and osteoarthritis increased the risk of certain geriatric syndromes. High rates of musculoskeletal morbidity are seen in the elderly in Pakistan. Measures at a health‐system level are required for better outcomes in older adults.